Development and Standardization of Ayurveda Mentioned Shadanga Panaya as a User-friendly Modern Pharmaceutical Oral Rehydration Powder - Jayathilake, R.M.D.; Karunagoda, K.P.K.R.; Dahanayake, J.M. (The University of Toronto, Canada, 2024)
hadanga Panaya is a compound Ayurvedic formulation that contains six ingredients: Cyperus rotundus L, Fumaria parviflora Lam, Vetiveria zizanoides L, Santalum album L, Pavonia odorata Willd, and Zingiber officinale Roscoe. As Shadanga Panaya is a decoction (Kashaya) mentioned in Ayurveda, Ayurvedic physicians have been using it to treat fever with thirst, Fever, Remove toxic substances from the blood (Raktapitta), Alleviate Pitta through sweating and address the burning sensation of the body and urination process, Diarrhea and vomiting like dehydration conditions. Symptoms of COVID-19 have also been treated with Shadanga Panaya. Standardization and quality parameters for Shadanga Panaya have not been reported. The aim of this research study was the development and standardization of the Ayurvedic formulation Shadanga Panaya into a user-friendly modern pharmaceutical oral rehydration powder. The study included a literature review on the method of preparation, Observation of the morphology of raw materials used, Preparation of Shadanga Panaya according to standard classical procedures and development of Shadanga Panaya using a spray dryer process without and with adding a filler (Maltodextrin) for a user-friendly dosage form. Comparisons were made regarding solubility, physicochemical analysis (Including pH, Refractive index and Specific gravity) and organoleptic properties (Color, odor, taste, and appearance) of the developed Shadanga Panaya according to World Health Organization (WHO) - 2012 guidelines. Standardization was performed to determine total ash content, acid-insoluble ash, water-soluble ash, and moisture content. The design and comparison of TLC fingerprinting, HPTLC, Analysis of electrolytes, Heavy metals and microbial contamination were conducted on the developed Shadanga Panaya. The spray-dried product was developed by adding Maltodextrin without any other excipients. The organoleptic properties met the standards of Ayurvedic preparation. Preliminary phytochemical screening revealed the presence of flavonoids, carbohydrates, saponins, phenols, and glycosides. Due to the importance of quality assessment and standardization, physicochemical evaluation was performed to set the standard. TLC fingerprinting showed separation in the aqueous extract of Shadanga Panaya, using a solvent system of Chloroform: Acetone: Glacial acid (15.2:3:1). This system was found to be optimal for chromatography. A comparative TLC study showed identical components between the developed Shadanga Panaya powder and its ingredients. Thus, TLC can be considered an essential tool for quality control measures of Shadanga Panaya, Helping to establish its identity, Degree of purity and quality as quality assurance standards. This will increase the acceptance of Shadanga Panaya without compromising human health in the present scenario. The pH was 6.70, The refractive index was 0.1 and the specific gravity was 1.0085. The electrolyte composition and pH of the product did not meet the composition of Oral Rehydration Solution according to the WHO that identified and will be corrected by further studies. The research team believes that with the new approach, standardization and evaluation of standard operation procedures will be able to develop Shadanga Panaya as a user-friendly Oral Rehydration Powder according to WHO guidelines to emphasize the potential for innovation and enhanced treatment outcomes in future healthcare.
Keywords: Herbal powder Standardization parameters; Oral rehydration therapy; Product development technology; Shadanga Panaya; TLC; WHO guidelines